Detection of intestinal dysplasia using angle-resolved low coherence interferometry - Terry, Neil (Society of Photo-Optical Instrumentation Engineers (SPIE), 2011)
Angle-resolved low coherence interferometry (a/LCI) is an optical biopsy technique that allows for depth-resolved, label-free measurement of the average size and optical density of cell nuclei in epithelial tissue to assess the tissue health. a/LCI has previously been used clinically to identify the presence of dysplasia in Barrett's Esophagus patients undergoing routine surveillance. We present the results of a pilot, ex vivo study of tissues from 27 patients undergoing partial colonic resection surgery, conducted to evaluate the ability of a/LCI to identify dysplasia. Performance was determined by comparing the nuclear morphology measurements with pathological assessment of co-located physical biopsies. A statistically significant correlation between increased average nuclear size, reduced nuclear density, and the presence of dysplasia was noted at the basal layer of the epithelium, at a depth of 200 to 300 μm beneath the tissue surface. Using a decision line determined from a receiver operating characteristic, a/LCI was able to separate dysplastic from healthy tissues with a sensitivity of 92.9% (13/14), a specificity of 83.6% (56/67), and an overall accuracy of 85.2% (69/81). The study illustrates the extension of the a/LCI technique to the detection of intestinal dysplasia, and demonstrates the need for future in vivo studies.